Jerónimo Martins´ adaption to a new reality / the growth and expansion through e-commerce for Jerónimo Martins - Santos, Jéssica Rosário (2022)
Jerónimo Martins operates in Portugal, Poland, and Colombia, through food retail and distribution. The company is listed on the Euronext Lisbon Stock Exchange and is part of the PSI20 index, with a share capital of 629 million euros. The study of the company was based on market economic trends, on the industry in which it is positioned, and on a comparative analysis between Jerónimo Martins and its peers. The analysis was based on the DCF and Multiple Valuations. Thus, in December 2022, the projected share price is 23,41€,obtaining a total return for the investor of 15,80%, buy position.